Non-contiguous finished genome sequence and description of Gorillibacterium massiliense gen. nov, sp. nov., a new member of the family Paenibacillaceae. Issue 3 (November 2014) - Keita, Mamadou; Padhmanabhan, Roshan; Caputo, Aurélia; Robert, Catherine; Delaporte, Eric; Raoult, Didier; Fournier, Pierre-Edouard; Bittar, Fadi
Abstract Strain G5T gen. nov., sp. nov. is the type strain ofGorillibacterium massiliense, a newly proposed genus within the familyPaenibacillaceae . This strain, whose genome is described here, was isolated in France from a stool sample of a wildGorilla gorilla subsp.gorilla from Cameroon.G. massiliense is a facultatively anaerobic, Gram negative rod. Here we describe the features of this bacterium, together with the complete genome sequence and annotation. The 5, 546, 433 bp long genome (1 chromosome but no plasmid) contains 5, 145 protein-coding and 76 RNA genes, including 69 tRNA genes.